Tracheostomy in pediatric critically ill patients - Caprotta, Gustavo (J Pediatr Intensive Care, 2012)
The indications for and timing of tracheostomy in children have changed significantly over recent years, and no consensus has been gathered in that regard. The purpose of this study is to present a series of critically ill patients who required a tracheostomy. All critically ill patients required a tracheostomy between 1 June 2009 and 31 March 2012. It is a retrospective, observational, descriptive study. A total of 18 patients underwent tracheostomy during the period under study. The most common indication was neuromuscular compromise. The average duration of mechanical ventilation before placement of a tracheostomy was 23.8 days (0–58 days). The complications observed were minor, and no patients died from tracheostomy-related causes. All parents were trained in airway management and cardiopulmonary resuscitation. There were no serious tracheostomy-related complications in critically ill pediatric patients. The procedure was effective in the management of patients with respiratory failure, patients with neuromuscular compromise and children with upper airway obstruction.